2020
DOI: 10.1098/rspb.2020.0980
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect effects of environmental toxicants on the health of bumblebees and their microbiomes

Abstract: Bumblebees ( Bombus spp.) are important and widespread insect pollinators, but the act of foraging on flowers can expose them to harmful pesticides and chemicals such as oxidizers and heavy metals. How these compounds directly influence bee survival and indirectly affect bee health via the gut microbiome is largely unknown. As toxicants in floral nectar and pollen take many forms, we explored the genomes of bee-associated microbes for their potential to detoxify cadmium, copper, selenat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 90 publications
(102 reference statements)
1
31
0
Order By: Relevance
“…To characterize the bacterial community in each gut, we then prepared amplicon libraries using the 799F ( CMGGATTAGATACCCKGG )-1115R ( AGGGTTGCGCTCGTTG ) 16S rRNA gene primers ( 57 , 58 ). We have used this primer pair extensively to prepare and sequence dual inline barcoded libraries ( 48 , 59 61 ). Briefly, we first included the partial Illumina sequencing adapter and a unique combination of 8-mer barcodes for each sample with primers that include the genomic primer sequence.…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the bacterial community in each gut, we then prepared amplicon libraries using the 799F ( CMGGATTAGATACCCKGG )-1115R ( AGGGTTGCGCTCGTTG ) 16S rRNA gene primers ( 57 , 58 ). We have used this primer pair extensively to prepare and sequence dual inline barcoded libraries ( 48 , 59 61 ). Briefly, we first included the partial Illumina sequencing adapter and a unique combination of 8-mer barcodes for each sample with primers that include the genomic primer sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Bees can be an indirect target of neonicotinoid insecticides such as IMI, thiacloprid, nitenpyram, amitraz and dimethoate. Several studies suggested that long-term exposure can lead to impairment of the gut microbial in bees with a reduced abundance of total bacterial flora, mainly Firmicutes [ 82 , 83 , 84 , 85 , 86 ]. In pregnant mice, nitenpyram also altered lipid metabolism and decreased the abundance of Proteobacteria , specifically of the Desulfovibrionaceae family [ 87 ], and IMI was shown to reduce liver weights and alter the histological structure of hepatic tissue, disrupting the gut microbial composition with consequently impaired barrier function [ 88 ].…”
Section: Insecticidesmentioning
confidence: 99%
“…Different threats have been identified to explain the global decline of bumblebees. For several years, many studies have explored effects of microbiota, diet, temperature, and pesticide exposure on bumblebee's health in lab conditions (Gill and Raine, 2014;Vanderplanck et al, 2019;Barraud et al, 2020;Rothman et al, 2020;Maebe et al, 2021a;Oyen et al, 2021). However, most of these studies used commercially available bumblebee species (i.e., Bombus impatiens in North America and B. terrestris in Europe, and Bombus hypocrita in Asia) which are known to be tolerant and resistant to environmental changes (Oyen and Dillon, 2018;Maebe et al, 2021b;Martinet et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%